Accounting in Ideal Conditions: Realizing Transparent and Accurate Accounting Practices - Tanfika Radita Putri; Lintang Febrianti; Lia Uzliawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine Accounting in Ideal Conditions: Realizing Transparent and Accurate Accounting Practices. The principles used in this study in realizing transparent and accurate accounting practices are responsibility, efficiency and effectiveness, and strategic vision. This type of research is qualitative research. Data collection techniques use literature studies. The results of the study indicate that accounting has a very important role in realizing transparency and accuracy. By realizing accountability, namely helping to improve performance and accountability of activities by compiling government agency performance accountability reports. In realizing transparency, accounting can guarantee the accuracy and reliability of the information to be disseminated, while in realizing responsibility, accounting helps to account for the use of regional revenue and expenditure funds by compiling financial reports. The role of accounting in realizing efficiency and effectiveness is to help process regional revenue and expenditure funds so that tasks and authorities are carried out optimally. The role of accounting in realizing a strategic vision is to prepare an optimal work plan by considering the planned results and costs incurred